The Influence of the Kaaba According to History in the Qur'an and Hadith on Islamic Architecture - Ghoffar, Abdul (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
This study examines the history of the Kaaba, the spiritual center and Islamic architecture, using a historical approach and linking it to the instructions in the Scriptures. Combining textual analysis and historical context, the author explores how the Kaaba is described and perceived in Islamic literature and how this is reflected in related architectural designs. Qualitative methods are used to interpret historical narratives about the Kaaba and to understand their implications for architectural practice in Islamic civilization. This research highlights the role of the Kaaba in shaping Muslim identity and spirituality and its relevance to Islamic architecture. The findings from this study provide a deeper insight into the relationship and relationships between the history of the Kaaba religion, the instruction of Kaaba in the Qur'an, Hadith, and architectural expressions, which relate to the function of space for worship activities that have the potential to enhance our understanding of the importance of the room of prayer (shalat). This worship activity is an Islamic spirituality that applies faithfulness (fidelity) and loyalty to the clarity of Islamic architecture.